Septic cardiopathy: disputable issues and prospects - I. A. Kozlov; I. N. Tyurin (Вестник анестезиологии и реаниматологии)
The objective: to present current information about definitions, etiopathogenesis, clinical, laboratory and hemodynamic manifestations of septic cardiopathy, based on published data and the results of our own research.Results: septic cardiopathy is the most important pathogenetic component of sepsis, and cardiac dysfunction makes a significant contribution to its outcomes. It is found out that after staying in the intensive care unit for 3-4 days, the level of the inactive part of the precursor of the B-type natriuretic peptide (NT-proBNP) > 3,450 pg/ml indicates of the risk of death: area under ROC curve (AUC) 0.708 (p = 0.0041), sensitivity 63.6%, and specificity 66.7%. At the same time, NT-proBNP > 5,250 pg/ml is associated with the use of inotropic drugs: AUC 0.769 (p = 0.0007), sensitivity 76.9%, specificity 79.0%. The article describes the detection of septic cardiopathy using transpulmonary thermodilution and calculation of such indices as afterload-related cardiac performance and cardiac function index. Data on the age-related parameters of central hemodynamics and risk of pathological decrease in certain blood circulation indices characteristic of older patients are presented. The article discusses the feasibility of treating septic cardiopathy as a variant of acute heart failure, which can be manifested not only by a decreased systolic function (low left ventricular ejection fraction) but also by increased end-diastolic pressure in the ventricles (diastolic dysfunction) with a normal left ventricular ejection fraction.